Perancangan Sistem E-Commerce untuk Transaksi Hasil Laut Berbasis Website - Tjandra, Stephen; Abdillah, Lufty (UNIVERSITAS KALBIS, 2024)
The Muara Baru Modern Fish Market, a fisheries business center, faces challenges due to the absence of an online system. Currently, customers must visit the store for purchases, and sellers cannot update product information or process transactions online. Additionally, sales reports are manually recorded using paper or books, affecting business efficiency. To address these issues, a study proposes the design of an e-commerce system using PHP programming and the prototyping method. Black Box Testing will be employed for evaluation. Data collection involves observations, interviews, and literature studies. The envisioned e-commerce system will enable customers to access real-time product information, place orders, and make online payments, streamlining the buying process. This website-based seafood transaction system is expected to enhance customer convenience and operational efficiency, providing a robust solution for Muara Baru Modern Fish Market to thrive in the digital era.